PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS BELAJAR KIMIA SISWA - Diska Vera Santi; Dewi Handayani; Nana Noviyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This research was conducted with the aim of describing the application of the Problem Based Learning (PBL) model with multimedia assistance to learning activities and student learning outcomes of class XII MIPA C SMA Negeri 6 Bengkulu City in the Faraday Law submission. This research was conducted in two cycles, with four stages, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. Teachers and all students of class XII MIPA C SMA Negeri 6 Bengkulu City for the academic year 2020/2021 were the subjects in this study, which was conducted on November 19, 2020 to November 27, 2020. Based on the results of the research that has been carried out, increased teacher and student activity and results student learning increases with each cycle. Teacher activity has increased by an average of 23 in cycle I and increased to 25.5 in cycle II. The results of the average student activity in the first cycle was 20 and increased to 25 in the second cycle. Likewise with the student's cognitive learning outcomes, which also increased from the first cycle, namely 41.67 to 80.3 in the second cycle. It can be said that the application of the Problem Based Learning model with the assistance of ultimedia in Faraday's Law submission is able to improve learning activities and student learning outcomes.